Design, Development and Implementation of a Low Cost Weather Station for high mountains - Leon J.L. (2021)
ACKNOWLEDGMENT We thank the INAIGEM for accomplish the Project “Evaluación y estimación de la distribución espacio temporal de permafrost a nivel nacional como potencial de reserva hídrica - PERMAFROST” and CONCYTEC-FONDECYT for funding (call number E041-01, contract number N°23-2018-FONDECYT-BM-IADT-MU).